An attempt to attribute the authorship of the treatises from the collection “The Modern Musick-Master” (London, 1730). - Alexei A. Panov; Ivan V. Rosanoff (Современные проблемы музыкознания, 2021)
In 1730, a collection of treatises on singing and playing various musical instruments was published in London. It included “A Brief History of Music” and a small musical dictionary. Neither on the title page nor elsewhere in the text do we find information about its author/authors. Today, both reference and encyclopedic literature as well as special scholarly works refer to Peter Prelleur as the author (very rarely the compiler) of the collection. However, when comparing the basic explanations of musical theory and the basic performing principles in each individual treatise, these explanations turn out to be contradictory. The article provides a comparative analysis of the materials in the collection itself and in the works published in England from the middle of the 17th century to 1730. Based on the results of the analysis and the data obtained from modern research, the authors come to the conclusion that all the sections of the collection in question represent a compilation of materials. The materials came from previously published manuals written by English, French and Italian musicians and were then supplemented by theoretical and performance guidelines relevant for those days. In general, the collection is a perfect example of pirate traditions of English book publishers of the 18th century. It is safe to say that “The Modern Musick-Master” was a collective effort and Peter Prelleur was not its only author or compiler.